A precise mass measurement of PSR J2045 + 3633. Issue 3 (2nd October 2020) - McKee, J W; Freire, P C C; Berezina, M; Champion, D J; Cognard, I; Graikou, E; Guillemot, L; Keith, M J; Kramer, M; Lyne, A G; Stappers, B W; Tauris, T M; et al.
ABSTRACT: We present the results of a timing analysis undertaken with the goal of obtaining an improved mass measurement of the recycled pulsar J2045 + 3633. Using regular high-cadence observations with the Effelsberg, Nançay, and Lovell radio telescopes, together with targeted campaigns with the Arecibo Telescope and Effelsberg, we have assembled a 6-yr timing data set for this pulsar. We measure highly significant values for the proper motion and the related rate of change of orbital semimajor axis ($\dot{x}$ ), and have obtained high-precision values of the rate of advance of periastron time ($\dot{ω }$ ), and two of the Shapiro delay parameters ( h 3 and ς). This has allowed us to improve the measurements of the pulsar and companion masses by an order of magnitude, yielding (with 1 σ uncertainties) $1.251^{+0.021}_{-0.021}\, \text{M}_{\odot }$ for PSR J2045 + 3633, and $0.873^{+0.016}_{-0.014}\, \text{M}_{\odot }$ for its white dwarf companion, and has allowed us to place improved constraints on the geometrical orientation of the binary system. Using our measurements of the binary component masses and the orbital size, we consider possible evolutionary scenarios for the system.